1993
DOI: 10.3109/00016359309041145
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and inter-individual variation in salivary flow rate, buffer effect, lactobacilli, and mutans streptococci among 11- to 12-year-old schoolchildren

Abstract: Both intra- and inter-individual variation in salivary flow rate, buffer effect, and the levels of salivary mutans streptococci and lactobacilli were analyzed in 128 11-year-old children. The follow-up period was 9 months, with six saliva samplings done at regular intervals. Inter-individual variation was relatively large in paraffin-stimulated salivary flow rate: low (< 1.0 ml/min) and high (> or = 2.0 ml/min) flow rates were measured in 18% and 13% of the children, respectively. Intraindividual variation dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 26 publications
4
17
1
Order By: Relevance
“…Other studies support our finding as they have reported that larger quantities and faster rates of acid production in caries active individuals than that in caries-free individuals [41,42]. There is strong evidence showing that salivary buffering capacity protects the tooth from dental caries [43] and low buffering capacity is usually associated with caries development because of its impaired neutralization of plaque acids and reduced remineralization of early enamel lesions [44][45][46]. This association between low caries levels and high salivary buffering capacity has been demonstrated [47,48] and individuals with a high salivary buffer capacity are often cariesresistant [11].…”
Section: Discussionsupporting
confidence: 87%
“…Other studies support our finding as they have reported that larger quantities and faster rates of acid production in caries active individuals than that in caries-free individuals [41,42]. There is strong evidence showing that salivary buffering capacity protects the tooth from dental caries [43] and low buffering capacity is usually associated with caries development because of its impaired neutralization of plaque acids and reduced remineralization of early enamel lesions [44][45][46]. This association between low caries levels and high salivary buffering capacity has been demonstrated [47,48] and individuals with a high salivary buffer capacity are often cariesresistant [11].…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, we did not find any relationship between the biochemical salivary factors assessed at baseline and the subsequent enamel demineralization observed. These findings are in agreement with those of some authors 9 but differ from the results of others 19 . Our data support the report that the association between these factors and caries activity is weak, suggesting their use in a longitudinal and regular follow-up of a patient 18 , rather than as caries predictors.…”
Section: Discussionsupporting
confidence: 71%
“…However, the low levels of mutans streptococci found in the saliva of the volunteers may have contributed to the lack of relationship found in this study. Using populations with wide-ranging levels of mutans streptococci in saliva, some studies were able to find a relationship between them and present or future dental caries experience 9,19 . In addition, the present study also did not find a relationship between enamel demineralization and the proportion of mutans streptococci in the plaque formed (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the salivary ms level of a subject were permanently high, the exposure time and, therefore, the risk for caries would be higher than if the level fluctuated [Manji and Nagelkerke, 1990]. For this reason, multiple salivary samples have been collected from each individual, with varying intervals ranging from hours to months [Togelius et al, 1984;Matee et al, 1985;Bentley et al, 1988;Bratthall and Carlsson, 1989;El Nadeef and Bratthall, 1991;Tukia-Kulmala and Tenovuo, 1993;Petti and Tarsitani, 1998]. …”
mentioning
confidence: 99%